2019
DOI: 10.3393/ac.2018.10.15.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Delorme-Thiersch Operation Outcomes in Men and Women With Rectal Prolapse

Abstract: PurposeThe laparoscopic rectopexy has become increasingly popular with verified stability, surgical route selection should be tailored to individual patient characteristics rather than operative risk. The perineal approach is useful in young male patients who need to preserve fertility. This study aimed to compare the characteristics of men and women who underwent Delorme-Thiersch procedures and analyze the postoperative outcomes of the perineal approach by sex.MethodsWe retrospectively reviewed the medical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Previous studies reported that the rate of recurrence after Delorme’s procedure ranged from 9.6% to 29.7% [ 6 , 8 , 13 - 15 , 18 - 21 ]. The rate of recurrence in this current study was 27.1%, which is relatively higher than previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that the rate of recurrence after Delorme’s procedure ranged from 9.6% to 29.7% [ 6 , 8 , 13 - 15 , 18 - 21 ]. The rate of recurrence in this current study was 27.1%, which is relatively higher than previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariable Cox proportional hazards regression models were subsequently fitted to evaluate factors independently associated with RFT. Patient age, sex, length of the prolapsed rectum, and variables found to have a P-value of < 0.20 in univariate analysis were included in the multivariate analysis models [ 8 , 13 , 14 ]. Results are presented as hazard ratios (HRs) and 95% confidence intervals (CIs).…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, the Thiersch operation is usually performed in addition to other surgical procedures. A modified Gant–Miwa–Thiersch procedure [ 18 ] and the Delorme–Thiersch operation [ 19 ] for rectal prolapse were reported with recurrence rates of 7.5% and 7.8%, respectively. Therefore, an additional Thiersch operation, among other procedures, is effective for both decreasing the incidence of recurrence for rectal prolapse and improving fecal incontinence.…”
Section: Discussionmentioning
confidence: 99%
“…All meshes used were made of polypropylene materials. Perineal approach included Delorme procedure, Thiersch procedure, Delorme with Thiersch procedure, and Altemeir procedure [ 18 19 20 21 22 ]. With a Thiersch procedure, a non-absorbable suture material was placed circumferentially around the anus, allowing an index finger to pass through [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…With a Thiersch procedure, a non-absorbable suture material was placed circumferentially around the anus, allowing an index finger to pass through [ 22 ]. The Delorme with Thiersch procedure was mainly performed in Song Do Hospital (Seoul, Korea) [ 20 ]. After the Delorme procedure, a polyester tape (Cervix set, B Braun, S.A., Rubí, Spain) was brought through the tunnel around the external anal sphincter to encircle the anal canal.…”
Section: Methodsmentioning
confidence: 99%